Stock market liquidity and economic resilience in Malaysia during COVID-19: Implications for financial stability and sustainable development - NGUYEN, Dung Duc; VU, Thu Thi Minh; NGUYEN, Ha Linh; NGUYEN, Dao Thi; NGUYEN, Thu Hang (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the liquidity dynamics of the Malaysian stock market during and after the COVID-19 pandemic, focusing on the 361-day period surrounding the pandemic's onset. By employing multivariate regression models, the research examines how key factors, such as trading volume, market volatility, and price fluctuations, impacted liquidity in Malaysia during this period of unprecedented market disruption. Two primary liquidity measures—Amihud's illiquidity ratio and bid-ask spreads—are utilized to capture different dimensions of market liquidity. The results highlight the significant effect of the pandemic's initial impact on liquidity, with both increased market volatility and shifts in trading volumes contributing to a marked deterioration in market efficiency. The findings reveal that liquidity challenges were most acute in the early stages of the pandemic, characterized by wider bid-ask spreads and heightened illiquidity. However, over time, the Malaysian market demonstrated resilience, with liquidity conditions improving as volatility subsided and market activity stabilized.